Gender Influence on In-hospital Outcomes of Primary Percutaneous Coronary Intervention (Bangladesh Heart Journal, 2022)
Background: Acute myocardial infarction (AMI) is one of the leading cause death and disability all over the world. But, there is a lack of data about the gender influence on in-hospital outcomes of primary percutaneous coronary intervention (pPCI) among Bangladeshi patients. This study was aimed to evaluate the clinical and angiographic differences and to compare their in hospital outcomes of pPCI between male and female patients. Objective: To evaluate the gender influence on in-hospital outcome of primary PCI. Methods: This was a prospective observational study of 90 patients with ST elevation myocardial infarction ( STEMI ) treated with pPCI in the Department of Cardiology, NICVD, Dhaka, Bangladesh from April 2019 to March 2020, followed from admission until hospital discharge or death. The patients were divided equally into two groups, group ‘! (female) and group a! (male). Result : A significant difference was observed for age (61.8±10.9vs.56.5±10.7 years; p=0.02), hypertension (66.7% vs. 42.2%; p=0.02), diabetes (68.9% vs. 44.4%; p=0.01), smoking (0.0% vs. 68.9%; p